Estratégias na indústria de motocicletas: um estudo exploratório do setor de motocicletas brasileiro - Marim, Daniel (2010)
In recent years, Brazil's motorcycle industry has become highly competitive and has been prominent in the industrial economy of Brazil. With the economic and social transformations that have occurred since 1994, is possible to attend that the landscape of this sector has been transformed, making the environment more competitive industries and organizations requiring fast and effective. This research studied the evolution undergone by Brazil's motorcycle industry, from 1970 to 2008, using as a reference the first installation of the multinational motorcycles in Brazil. The research is an exploratory and descriptive and aim to examine the strategic point of view, according to the typology of Miles and Snow (1978), Porter (1980), Hamel and Prahalad (1990) and Kim and Mauborgne ( 1998), the strategies adopted by major companies operating in the Brazilian motorcycle market. The companies studied were: Honda, Yamaha, Suzuki, Kazinski, Sundown and Dafra, which together comprised 97% market share in 2008 (FENABRAVE, 2009). First, was developed a literature describing the strategic typologies. Then, through a literature review, we attempted to present a brief overview of the motorcycle industry on the world set. From this first analysis, the study describes and examines the evolution of the motorcycle industry in the Brazilian market and the major changes ocurred. After this description, the research made an analysis of development of each company studied and the strategies used by each. Concluded the research with an analysis of strategies of each company from the point of view of strategic typologies presented in the theoretical framework